Analisis Fatwa DSN-MUI Nomor 25/III/2002 Terhadap Penetapan Ujrah Dalam Akad Rahn Di BMT UGT Sidogiri Cabang Waru Sidoarjo - M. Zainuddin Alanshori (Universitas Islam Lamongan, 2017)
Sharia financial institutions are financial institutions that not only prioritize profit oriented, but also a financial institution that also puts the public good in accordance with the demands of sharia which is the foundation of all Islamic financial institutions. One application is to implement a moral and spiritual based service. This field research will answer the question. First, how is application of ujrah determination in contract of rahn in BMT UGT Branch Sidogiri Waru Sidoarjo? The second, how is the analysis of the DSN-MUI fatwa NUMBER 25/III /2002 on the determination of ujrah in the contract of rahn in BMT UGT Branch Sidogiri Waru Sidoarjo? Data collection techniques used are interview, document review, and observation, then analyzed by using descriptive analysis method, with deductive thought pattern, that is theory of rahn, ijarah, and fatwa of National Sharia Council (DSN) with general characteristics and then linked with the facts on the ground about the fatwa of DSN-MUI NUMBER 25/III/2002 on the establishment of ujrah in the contract of rahn in BMT UGT Branch Sidogiri Waru Sidoarjo with special characteristics. From the results of the study, the author concludes the application of the determination of ujrah in the covenant of rahn in BMT UGT Branch Sidogiri Waru Sidoarjo, namely the determination of ujrah through two contracts, namely rahn and ijarah contract. The procedures for the implementation of the contract are as follows: Rahin (customer) comes to murtahin (BMT) while delivering marhun (collateral goods) then the goods will be estimated. As a result of this, the rahin will be subject to administrative costs. Then rahin signs the agreement or contract of rahn. After that, to entrust the goods hock, rahin must implement contract of ijarah (contract to rent place). Consequently it arise ujrah. In this case, it means that customer must implement two barrage of contract. The determination of ujrah applied in BMT is not in accordance with the Fatwa DSN-MUI NO: 25/DSN-MUI/ III/2002 because the determination of ujrah is determined from the amount of the customer’s loan, while the difference is the discount given to the customer for applying smaller loan. The determination of discount is determined from ujrah or ijarah fee charged to the customer. This discount is calculated based on the percentage of estimated value of customer’s loan amount. Keywords: Ujrah Determination, Rahn Contract, DSN-MUI Fatwa